2019
DOI: 10.36348/jaep.2019.v03i12.001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Appropriate Instructional Resources on Retention of Pupils with Disabilities in Mainstreamed Primary Schools in Bomet County, Kenya

Abstract: This research sought to find out the influence of appropriate instructional resources on retention of pupils with disabilities in mainstreamed Primary Schools in Bomet County, Kenya. The challenge that this study sought to address was low retention of Pupils with Disabilities (PWDs) in mainstreamed schools. This study was embedded in Systems Theory by Von Bertalanffy [1]. It adopted survey research design. The target population was 840 teachers. Yamane formula was applied to get a sample size of 278 teachers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
0
0
Order By: Relevance
“…These findings are also supported by those of Deveci et al (2023) which indicated that relevant teaching materials had a significantly positive impact on the learning process. Kipkirui et al (2019) revealed that appropriate instructional materials influenced retention of pupils with disabilities.…”
Section: Hypothesis Testingmentioning
confidence: 99%
“…These findings are also supported by those of Deveci et al (2023) which indicated that relevant teaching materials had a significantly positive impact on the learning process. Kipkirui et al (2019) revealed that appropriate instructional materials influenced retention of pupils with disabilities.…”
Section: Hypothesis Testingmentioning
confidence: 99%